Hubungan antara Stres Psikologis pada Siswi kelas 3 Menjelang Ujian Nasional dengan Angka Kejadian Dysmenorrhea Primer di SMA Negeri 2 Magelang - MY. Cendy Nindra Brilliana; yulia lanti retno dewi; slamet riyadi (Nexus Kedokteran Komunitas, 2013)
Background: Upon approaching a menstruation or during the on-going menstruation phase, primary dysmenorrhea disorders are frequently found, particularly the pain in the lower abdomen, spreading to waist and thigh area which emerges without being accompanied by any gynecological anomalies. There are some factors assumed to play role in the occurrence of primary dysmenorrhea disorders. One of them is the psychological stress. The objective of this research is to investigate whether or not there is a correlation between the psychological stress of the students in Grade 3 upon approaching the National Test and the number of primary dysmenorrhea episodes at State Senior Secondary School 2 of Magelang. Method: This research used the observational analytical method with the cross-sectional approach. The research was conducted in March 2013. The samples of the research consisted of 95 students in Grade 3 of State Senior Secondary School 2 of Magelang and were taken by using the purposive sampling technique based on the inclusive criteria determined. The data of the research were gathered through in-depth interview and questionnaire. They were then analyzed statistically by using the Chi Square test and Lambda test. Result:The Chi Square test shows that the value of X2count is 9.342. This value is greater than that of X2table at the significance level of 5% with the independence level of 1, namely: 3.481 (p < 0.05). The result of the Lambda test is 0.118 with the p value = 0.436. Conclusion: Based on the result of the research, a conclusion is drawn that there is a very weak correlation between the psychological stress of the students in Grade 3 uponapproaching the National Test and the number of primary dysmenorrhea episodes at State Senior Secondary School 2 of Magelang. Keywords: primary dysmenorrhea; psychological stress